2022
DOI: 10.1186/s12931-022-02006-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined obstructive airflow limitation associated with interstitial lung diseases (O-ILD): the bad phenotype ?

Abstract: Background Patients suffering from combined obstructive and interstitial lung disease (O-ILD) represent a pathological entity which still has to be well clinically described. The aim of this descriptive and explorative study was to describe the phenotype and functional characteristics of a cohort of patients suffering from functional obstruction in a population of ILD patients in order to raise the need of dedicated prospective observational studies and the evaluation of the impact of anti-fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Among the 84 patients diagnosed with SAD, only 11 cases (11/84, 13%) had signi cant obstructive ventilatory dysfunction (FEV1/FVC < 0.7), which was slightly higher than the value of 7% (5/68) reported by Julien Guiotd [10]. In contrast, the majority of patients (87%) showed no signi cant obstructive ventilatory dysfunction by routine PFT.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Among the 84 patients diagnosed with SAD, only 11 cases (11/84, 13%) had signi cant obstructive ventilatory dysfunction (FEV1/FVC < 0.7), which was slightly higher than the value of 7% (5/68) reported by Julien Guiotd [10]. In contrast, the majority of patients (87%) showed no signi cant obstructive ventilatory dysfunction by routine PFT.…”
Section: Discussionmentioning
confidence: 69%
“…Few clinical studies have focused on ILD with small airway lesions. Julien Guiotd et al [10] have reported that about 15% of ILD patients are complicated with obstructive ventilator dysfunction. Among them, 7% (5/68) of patients have IPF comorbid obstructive ventilator dysfunction and impaired small airway function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 84 patients diagnosed with SAD, only 11 cases (11/84, 13%) had significant obstructive ventilatory dysfunction (FEV1/FVC < 0.7), which was slightly higher than the value of 7% (5/68) reported by Guiot et al (2022). In contrast, the majority of patients (87%) showed no significant obstructive ventilatory dysfunction by routine PFT.…”
Section: Discussionmentioning
confidence: 73%
“…Few clinical studies have focused on ILD with small airway lesions. Guiot et al (2022) have reported that about 15% of ILD patients are complicated with obstructive ventilator dysfunction. Among them, 7% (5/68) of patients have IPF comorbid obstructive Frontiers in Pharmacology frontiersin.org ventilator dysfunction and impaired small airway function.…”
Section: Discussionmentioning
confidence: 99%